Developing a running prototype of a bio-economic farm model for a trade-off analysis of different nutrient management options for maize cultivation in East-Africa - Hijbeek, Renske; Berge, Hein F.M. ten; Loon, Marloes P. van; Ittersum, Martin K. van (2018)
Considering projected population trends, food requirements in East Africa will drastically increase in the coming decades (van Ittersum et al., 2016). One way to ensure supply will meet demand is by raising crop yields in the region. In East Africa, agricultural yields still have large potential to increase due to the large gaps between actual and potential yields. A recent study has shown that intensification of agriculture in regions with low current yields (such as in East Africa) is an option to reduce greenhouse gas emissions by avoiding or reducing agricultural land expansion into forests and/or grasslands, thus preserving carbon stocks (Van Loon, Hijbeek, ten Berge and Van Ittersum 2018, in prep). This is however only valid if higher yields are obtained with highly efficient use of fertilisers. For a successful implementation of such climate smart agricultural intensification, improved nutrient management options need to be economically viable for farmers in East Africa. It is however often unclear under which conditions agricultural intensification is beneficial for farmers’ income in sub saharan Africa (Marenya and Barrett, 2009; Place et al., 2003; Sheahan et al., 2013). Besides a number of good agricultural practices (such as improving planting densities and sound crop protection measures), farmers need to apply more nutrients to intensify production. The amounts of additional nutrients required represents the ‘nutrient gap’ between current nutrient applications and the total amount of nutrients removed from fields with increased yields (de Vries et al., 2017). Farmers can use several nutrient management options to close the nutrient gap (e.g. use mineral or organic fertilisers, split application of fertilisers, combine with local or hybrid seeds). The nutrient management option a farmer chooses not only affects his or her nutrient use efficiency (how much of the applied nutrients are recovered by the crop), but also his or her income generation and the contribution to greenhouse gas emissions. Some practices might be most beneficial for farmers’ income, but have a larger contribution to greenhouse gas emissions. Others might have the reversed effect. So far, trade-offs and/or synergies between farmers’ income and greenhouse gas mitigation as a function of nutrient management options have not been systematically assessed. Additionally, it is uncertain how such trade-offs or synergies might evolve over time, in cases where soil carbon and nutrient pools respond over longer time frames to the management exposed. We therefore address the following question: Can certain nutrient management practices be identified which are beneficial for both climate change mitigation and for farmers’ income in East Africa? The aim of this report is to develop a running prototype of a bio-economic model which can be used to assess trade-offs between yields, farmers ‘income and greenhouse gas emissions in function of different nutrient management options, both on the short and the long term. The proposed model will focus on nitrogen (N) as the main limiting nutrient, which is also highly relevant for greenhouse gas emissions (i.e. N2O). The model will be useful for R&D investors, agri-business (including fertiliser companies) and government agencies for ex ante assessment of specific nutrient management options.